The Role of Emotions in the Work Inclusion of People with Disabilities - Marta Nogueira (2021)
The labor inclusion of people with disabilities (PcD's) is one of the most important points for their inclusion in society. Despite the constant evolution in legislation, people with disabilities still don't have the same access to job opportunities as their non-disabled colleagues. It is urgent to fight the stigma related to this population. In this sense, this study contributed to the deepening of the knowledge that people with disabilities (PcD's) have about their emotions in the workplace, as well as about their inclusion process, bringing suggestions for improvement about this very pertinent social issue. The following specific objectives were defined: to know the degree of awareness that workers with disabilities have about their emotions in their daily interactions at their workplace and, to verify to what extent the Convention on the Rights of Persons with Disabilities has improved the inclusion process. In this study, qualitative research was chosen, using semi-structured interviews. The sample was composed of 50 workers with disabilities, employees of the Auchan Portugal Group. The results showed that PwD's recognize their emotions when interacting with their co-workers. However, most of these people disguise the discomfort felt, not communicating clearly which emotions they felt. In addition, it was found that, although most PcD's feel included, it suggests greater sensitivity from the employer, work adapted to the person and their disability, and more accessibility in the workplace.